Pogłoska prasowa jako komponent gazet rękopiśmiennych z drugiej połowy XVIII wieku (na materiale tekstów Jędrzeja Kitowicza) (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
In this article, I discuss the importance of press rumours in the organising of handwritten newspapers from the second half of the 18th century written by Jędrzej Kitowicz. The discussion is preceded by the communication characteristics of rumour and press rumour, as well as the communication phenomenon of newspapers written in the 18th century in Poland to order by powerful people. Particular attention was paid to the features of the handwritten press and their relationship to the structure of their texts. The press rumour was shown as an informative genre specific to this type of press, responding to the communication needs of the audience. The analysis of the rumour texts focuses on genre-specific indicators, particularly those indicating the degree of reliability of the information.